MENINGKATKAN KOMPETENSI GURU SDN 007 KAMPUNG BARU KECAMATAN CERENTI DALAM MENYUSUN PERENCANAAN PEMBELAJARAN MELALAUI SUPERVISI AKADEMIK - Suriati Suriati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is based on the result of supervision that has been done in the teacher of Public SDN 007Kampung Baru Kecamatan Cerenti. the weakness of teachers in preparing the learning implementation plan liesin the integration of the material with the method, as well as the media used. Based on the findings of theexisting teachers still use the learning implementation plan which is downloaded from the internet then in editidentity while the contents of the lesson plan is not revised. So that the existing planning sometimes does notmatch what is done in the field. Another problem is the lack of teacher awareness of the importance of a plan inimplementing an action in learning. This research aims to improve the ability of teachers in mempuun learningimplementation plan. Improving the ability of teachers to choose appropriate methods in preparing the lessonplans. From the analysis of data seen In the components formulation of indikators of learning objectives, seen anincrease from 60% on initial ability, to 65% in cycle 1 and increased to 70% at the end of the activity. In thecomponent determination of learning strategies, there is an increase in ability from 65% to 70% after cycle 1and more strengthened to 80%. In the component selection of teaching learning materials, from the original65% increase is very significant to 85%. In the selection component Media and learning tools there is also anincrease from 70% at the beginning of activities and after cycle 1, to 75% after cycle 2. Looking at the data ofresearch findings in this school action research activity, it can be concluded that the academic supervisionconducted by the principal of 5 teachers who have no teacher education background, succeeded in increasingtheir pedagogic competence in developing learning planning.